UJI DAYA HAMBAT Streptomyces roseoflavus AL2 TERHADAP Xanthomonas sp. PENYEBAB PENYAKIT HAWAR DAUN BAKTERI (HDB) PADA TANAMAN PADI (Oryza sativa L.) - Nellawati, Ni Luh Cipta Ayumi; Kawuri, Retno; Arpiwi, Ni Luh (Metamorfosa: Journal of Biological Sciences; Vol 3 No 1 (2016)DO - 10.24843/metamorfosa.2016.v03.i01.p01, 2016)
The purpose of this study was to determine the potential of Streptomyces in inhibiting the growth of pathogenic bacteria causing bacterial leaf blight (BLB) in vitro and identify the most likely type of Streptomyces that inhibits the growth of pathogens in the HDB. Bacterium Xanthomonas sp. used in this study were isolated from sick rice plants in Ayunan Village, Badung, Bali while Streptomyces isolates were isolated from the rhizosphere of reed plants (AL2), lily (LL1 and LL2), Aloe Vera (AV) and Elephant Grass (RG) from 3 different locations, namely PT. Alove Gianyar, Bedugul Botanical Garden and Buruan Village, Gianyar. Test results of antagonist test using dual culture method at the PCA medium showed that Streptomyces sp. AL2 has the most percentage of inhibition compared with other Streptomyces sp. isolates against pathogenic bacteria., namely 17.8 mm. The results of identification using the book Guide to the Classification and Identification of the Actinomycetes and Their Antibiotics (Waksman and Lechevalier, 1973) showed that the Streptomyces sp. AL2 is Streptomyces roseoflavus . The results provide an early indication that the filtrate of Streptomyces AL2. has the potential to be developed as a biocontrol of biological bactericide.
Keywords: Rice, Bacterial leaf blight, Xanthomonas sp., Streptomyces roseoflavus AL2